1985
DOI: 10.1002/mrd.1120120408
|View full text |Cite
|
Sign up to set email alerts
|

7‐aminoactinomycin D binding and the final stages of sperm chromatin processing in the mouse

Abstract: Quantitative fluorescence microscopy is used to compare the binding of the fluorescent, 7‐amino derivative of actinomycin D to a sonication resistant fraction of late‐step mouse spermatids and sperm isolated from three regions of the epididymis. Staining conditions are described that optimize 7‐AMD binding to air‐dried smears of these cells and permit quantitative analyses of 7‐AMD binding to sperm chromatin at the single cell level. These studies show that the step 12–16 spermatid undergoes an 8–10‐fold reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…For example, the similarity between the 7-AMD fluorescence pattern and that of the externally binding antibiotics (MA, CMA3, and OM), can be interpreted as resulting not only from their common GC specificity but also from a preferential extemal binding mode of the 7-AMD. Although the external and intercalating binding modes have been suggested for 7-AMD (Gill et al, 1975), the results reported here argue in favor of the extemal mode already reported to play an essential role in the stability of the DNA-7-AMD compound (Evenson et al, 1986;Balhorn et al, 1985). Another example is the similarity between the fluorescence pattern of QM-stained cells and that of AT-specific fluorochromes (HO and DAPI) with respect to both intra-and internuclear fluorescence distributions.…”
Section: Discussioncontrasting
confidence: 43%
“…For example, the similarity between the 7-AMD fluorescence pattern and that of the externally binding antibiotics (MA, CMA3, and OM), can be interpreted as resulting not only from their common GC specificity but also from a preferential extemal binding mode of the 7-AMD. Although the external and intercalating binding modes have been suggested for 7-AMD (Gill et al, 1975), the results reported here argue in favor of the extemal mode already reported to play an essential role in the stability of the DNA-7-AMD compound (Evenson et al, 1986;Balhorn et al, 1985). Another example is the similarity between the fluorescence pattern of QM-stained cells and that of AT-specific fluorochromes (HO and DAPI) with respect to both intra-and internuclear fluorescence distributions.…”
Section: Discussioncontrasting
confidence: 43%
“…Such a condition would not have been detected in our investigation since only amembranous nuclei were analysed. Similarly, it has been shown that spermatozoa from subfertile males are more susceptible to heat denaturation (Evenson et al, 1980 Staining nuclei with 7-AMD induced an increase in the size of the nuclei that may have been due to the prolonged exposure to either the dye or the buffer overnight (see Balhorn et al, 1985). However, the preferential increase in length may be related to the observation that chromatin, inside sperm nuclei, is in a cholesteric configuration (Sipski & Wagner, 1977 (Döring et al, 1972) failed to discriminate abnormal sperm heads from normal ones.…”
Section: Resultsmentioning
confidence: 99%
“…Sperm chromatin integrity (Gill et al, 1975) was assessed using the DNA intercalator 7-aminoactinomycin D (7-AMD; Calbiochem, San Diego, CA) as described by Balhorn et al (1985). Slides of dried nuclei were stained for 16 h in phosphate buffer (pH 70) containing 5 µ mol 7-AMD l"1.…”
Section: Isolation Of Sperm Nucleimentioning
confidence: 99%
“…Even mechanical breakage on DNA by sonication of nuclei renders DNA in higher-order chromatin structures intact under conditions where open chromatin sites coinciding with the DNase I hypersensitive sites are broken (Reneker and Brotherton 1991). An extreme example supporting the idea that higher-order chromatin structures are less accessible to damage arises from mature mammalian spermatocytes; due to a remarkable condensation of DNA brought about by the replacement of histones by protamines, sperm DNA is unreactive to benzpyrene (Balhorn et al 1985) and inaccessible to intercalation by actinomycin D (Darzynkiewicz et al 1969). The idea that higher-order chromatin structures might affect rates of damage has been previously discussed (Boulikas 1991(Boulikas , 1992.…”
Section: Higher-order Chromatin Structures Affect Rates Of Dna Damagementioning
confidence: 99%
“…DNA is neutralized, and the DNAprotamine complex is in a maximally condensed, biochemically inert state. The high affinity of protamines for the minor groove of DNA (Herskovits and Brahms 1976; Suau and Subirana 1977) and the marked insolubility that characterize the structure of the sperm chromatin render the DNA inaccessible to intercalating agents known to bind DNA in its minor groove such as actinomycin D (Darzynkiewicz et al 1969;Balhorn et al 1985). In addition, a mutagenic DNA alkylating agent, benzpyrene, which alkylates the N-2 position of guanine, is unable to damage sperm DNA (see Balhorn 1989).…”
Section: Preferential Damage and Repair In Germ-cell Lineagesmentioning
confidence: 99%